COMPUTERIZED RESERVATION SYSTEMS VIDEO SHOTING AND PHOTOGRAPHY "HORIZON" - Rizal Bin Tahir; Ida Ayu Wiasiti Drs. (Jurnal Sistem Informasi, 1997)
Reservation system that has been designed and which have been made then thesystem can help activities, ranging from receptionist to go to the studio and itsimplementation is no longer with the accounting manual. Reservation system that hasbeen proven using a computer services faster and more profitable in terms of thehandling of service orders and recording all transaction data.